UJI FITOKIMIA DAN ANTIOKSIDAN EKSTRAK ETANOL PROPOLIS LEBAH KELULUT (Tetragonula iridipennis) DARI SAMARINDA KALIMANTAN TIMUR - Binti Khairunnisa; Enih Rosamah; Harlinda Kuspradini; Irawan Wijaya Kusuma; Sukemi Sukemi; Nataniel Tandirogang; Enos Tangke Arung (Jurnal Ilmiah Manuntung, 2020)
The study aims to identify the secondary metabolite compounds contained in the ethanol extract Propolis Tetragonula Iridipennis and determine the antioxidant activity. Propolis is extracted from the beehive of Kelulut (Tetragonula Iridipennis) with a method of maceration of ethanol 96% produce a yield of 66.73%. Propolis extract contains alkaloid compounds, flavonoids, triterpenoids, tannins and carbohydrates. Propolis extract tested its antioxidant activity using the DPPH method (1.1-diphenyl-2-picrylhydrazyl) with a wavelength of 514 nm. Results showed a percentage of propolis extract free radicals 59% in concentrations of 100 ppm with IC50 33.74 ppm so that propolis extract is potentially as an antioxidant.